The effect of work-life balance and work-family conflict in determining life satisfaction and job satisfaction among employees in MPKu - Mohamad Kamsol, Naziha (2015)
Work-life balance plays its crucial role in helping employees to juggle their role between work and family domain. In an increasingly challenging world of employment, employees are exposed to work-family conflict i.e work-interference with family (WIF) and family-interference with work (FIW). Work-life balance as well as work-family conflict is closely related with the quality of life of individuals that involves life and job satisfaction. Hence, the purpose of this research is to study the role of work-life balance and work-family conflict in determining employees’ quality of life. The total respondents participated in this study were 113 which were taken from Majlis Perbandaran Kulaijaya (MPKu). A self-administered questionnaire was used for the data collection. The questionnaire used was to assess the level of work-life balance, work-family conflict as well as life and job satisfaction. The results from the analysis showed that the level of work-life balance among the employees at MPKu is at moderate level. Meanwhile, the level of work-family conflict is at low level for both WIF and FIW. The level of quality of life among the employees was reported at a moderate level which involves life satisfaction and job satisfaction. Linear regression analysis revealed that WIF was significantly has an effect on job satisfaction only while FIW was significantly has an effect on both life and job satisfaction. Findings from this study suggest that, future research should involve a larger sample size as it would give a clear picture of the organization. As for the organization, MPKu should take some actions in order to make the organization as a better place for work as job satisfaction was reported lower than the life satisfaction.